The gut-lung axis in the CFTR modulator era - Lussac-Sorton, Florian; Charpentier, Éléna; Imbert, Sébastien; Lefranc, Maxime; Bui, Stéphanie; Fayon, Michael; Berger, Patrick; Enaud, Raphaël; Delhaes, Laurence (Frontiers in Cellular and Infection Microbiology, 2023)
The advent of CFTR modulators represents a turning point in the history of cystic fibrosis (CF) management, changing profoundly the disease's clinical course by improving mucosal hydration. Assessing changes in airway and digestive tract microbiomes is of great interest to better understand the mechanisms and to predict disease evolution. Bacterial and fungal dysbiosis have been well documented in patients with CF; yet the impact of CFTR modulators on microbial communities has only been partially deciphered to date. In this review, we aim to summarize the current state of knowledge regarding the impact of CFTR modulators on both pulmonary and digestive microbiomes. Our analysis also covers the inter-organ connections between lung and gut communities, in order to highlight the gut-lung axis involvement in CF pathophysiology and its evolution in the era of novel modulators therapies.